1996
DOI: 10.1128/jvi.70.4.2394-2402.1996
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant adenovirus expressing an Epstein-Barr virus (EBV) target antigen can selectively reactivate rare components of EBV cytotoxic T-lymphocyte memory in vitro

Abstract: While the bulk of a virus-induced cytotoxic T-lymphocyte (CTL) response may focus on a few immunodominant viral antigens, in certain tumor virus systems the detectability of clones recognizing other, subdominantantigens can assume particular importance. By using the human CTL response to Epstein-Barr virus (EBV) as a model system, here we show that even rare components of virus-specific memory can be selectively reactivated in vitro when the relevant target antigen is expressed in autologous stimulator cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In this investigation we first evaluated CLG-specific responses in a group of HLA-A*0201-positive EBVseropositive individuals. Our results demonstrate that all donors have CLG-specific CTL precursors that can be reactivated by specific peptide stimulations, a finding which further favors the use of the CLG epitope as target of EBV-specific immunotherapies and the employment of specific stimulations to amplify a desired CTL population [6][7][8].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In this investigation we first evaluated CLG-specific responses in a group of HLA-A*0201-positive EBVseropositive individuals. Our results demonstrate that all donors have CLG-specific CTL precursors that can be reactivated by specific peptide stimulations, a finding which further favors the use of the CLG epitope as target of EBV-specific immunotherapies and the employment of specific stimulations to amplify a desired CTL population [6][7][8].…”
Section: Discussionmentioning
confidence: 61%
“…EBV induces long-lasting CTL memory, which is believed to play an important role in controlling EBV-carrying cells in the infected host. Thus, EBV-specific CTL precursors can be reactivated in a relatively large number from the peripheral blood of EBV-seropositive individuals by in vitro stimulation with autologous virus-infected B cells [5], or by selective stimulations [6][7][8]. Recent studies have shown that, in each individual, such CTL responses are a composite of several virus-induced reactivities [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…EBV, a widespread lymphotrophic herpes virus, induces long‐lasting CTL memory which is believed to play an important role in controlling EBV‐harboring cells in the infected host. Therefore, EBV‐specific CTL precursors can be reactivated from the peripheral blood of EBV‐seropositive individuals by in vitro stimulation with autologous LCL 18 or by selective restimulation 19, 20. In each individual, these CTL responses are a mixture of several virus‐induced reactivities, each reactivity being directed against one or more of the viral proteins presented in the context of particular HLA class I restriction determinants 8, 9, 21.…”
Section: Discussionmentioning
confidence: 99%
“…a Obtained by subtracting the lysis of target cells pulsed with the control peptide HIV-env from the lysis of target cells pulsed with peptide Rta [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The E/T ratio was 10:1. and target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Eight CTL lines recognizing the seven different epitopes were examined in this way; six lines showed reactivity against the vaccinia virus-infected cells, whereas two (B-3 and E-1, specific for peptides Rta-67 and Rta-50, respectively) obviously were not able to kill vaccinia virus-infected cells. Inappropriate processing of vaccinia virus antigens has been described (2,45); in such cases, CTL reactivities against a certain protein or epitope can be demonstrated by use of target cells transiently transfected with an expression vector for the protein in question or by application of other, e.g., adenovirus-based, expression systems (32,42).…”
Section: Discussionmentioning
confidence: 99%